Prevention of trauma-induced cochlear fibrosis using intracochlear application of anti-inflammatory and antiproliferative drugs. (1st March 2016) - Jia, H.; François, F.; Bourien, J.; Eybalin, M.; Lloyd, R.V.; Van De Water, T.R.; Puel, J.-L.; Venail, F.
Highlights: Inflammation and epithelial to mesenchymal cell transition are involved in cochlear fibrosis. Dexamethasone and aracytine both prevent fibrosis in the cochlea. Analysis of the risk/benefit ratio favors the use of Ara-C to prevent cochlear fibrosis. Abstract: Cochlear fibrosis is a common finding following cochlear implantation. Evidence suggests that cochlear fibrosis could be triggered by inflammation and epithelial-to-mesenchymal cell transition (EMT). In this study, we investigate the mechanisms of cochlear fibrosis and the risk/benefit ratio of local administration of the anti-inflammatory drug dexamethasone (DEX) and antimitotic drug aracytine (Ara-C). Cochlear fibrosis was evaluated in cochlear fibrosis models of rat cochlear slices in vitro and in KLH-induced immune labyrinthitis and platinum wire cochlear implantation-induced fibrosis in vivo . Cochleae were invaded with tissue containing fibroblastic cells expressing α-SMA (alpha smooth muscle actin), which along with collagen I, fibronectin, and laminin in the extracellular matrix, suggests the involvement of a fibrotic process triggered by EMT in vitro and in vivo . After perilymphatic injection of an adenoviral vector expressing GFP in vivo, we demonstrated that the fibroblastic cells derived from the mesothelial cells of the scalae tympani and vestibuli. Activation of inflammatory and EMT pathways was further assessed by ELISA analysis of the expression of IL-1β and TGF-β1. Both markers were elevated in vitro and in vivo, and DEX and Ara-C were able to reduce IL-1β and TGF-β1 production. After 5 days of culture in vitro, quantification of calcein-positive cells revealed that Ara-C was 30-fold more efficient in preventing fibrosis, and provoked less sensory hair cell loss, than DEX. In KLH-induced immune labyrinthitis and platinum wire-implanted models, Ara-C was more efficient in preventing proliferation of fibrosis with less side effects on hair cells and neurons than DEX. In conclusion, DEX and Ara-C both prevent fibrosis in the cochlea. Analysis of the risk/benefit ratio favors the use of Ara-C for preventing cochlear fibrosis.